EFFECT OF METRIBUZIN IN COMBINATION WITH POST EMERGENCE HERBICIDE ON WEED AND PRODUCTIVITY OF WHEAT - A. H. NANHER, RAGHUVIR SINGH, SHASHIDHAR YADAV, SACHIN TYAGI, VINOD KUMAR, ASHUTOSH KUMAR SINGH SHAMIM AKHTAR SHAMIM, (The Bioscan, 2015)
A field experiment was conducted in wheat during rabi season 2011-12 on sandy loam soil at Crop Research Centre, Chirodi of SardarVallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.). The results indicated that chemical methods of weed control Sulfosulfuron+ metribuzin @ 25 + 105 g a.i ha-1 (T7) as post emergence controlled the narrow and broad leaves weeds very effectively and recorded higher value of WCE (89.89%) followed by a combination of sulfosulfuron+ carfentrazone. 25 + 40 g a.i ha-1 (T8), and clodinafop+ metribuzin @ 60 + 122.5 g a.i ha-1(T5) as post emergence respectively. Highest grain yield (55.13q/ha-1), and straw yield (78.08 q/ha-1), was recorded under sulfosulfuron.+ metribuzin @ 25 + 105 g a.i ha-1(T7), maximum net return and B-C ratio was recorded with sulfosulfuron.+ metribuzin @ 25 + 105 g a.i ha-1 (T7) as post emergence (Rs. 63453.59/ha) and (2.48), followed by clodinafop+ metribuzin @ 60 + 122.5 g ha-1 as post emergence ((62820.04/ha) and (2.45) respectively.